1996
DOI: 10.2307/1166205
|View full text |Cite
|
Sign up to set email alerts
|

Interviewing Young Children about Body Touch and Handling

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
93
4
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 295 publications
(233 reference statements)
7
93
4
1
Order By: Relevance
“…Thus, if something is routinely recalled, it seems to be reliably accurate. This difference in accuracy depending upon frequency of recall was also noted by Steward et al (1996).…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Thus, if something is routinely recalled, it seems to be reliably accurate. This difference in accuracy depending upon frequency of recall was also noted by Steward et al (1996).…”
Section: Discussionsupporting
confidence: 58%
“…Since the same questions are asked in each interview in this study, it is not surprising that children's recall is much more consistent than in the interviews of Fivush and Hudson, among others (Fivush and Hamond, 1990;Fivush and Shukat, 1995;Hudson, 1990;Hudson and Fivush, 1991) in which questions often differed substantially between interviews. Less straightforward are differences with Steward et al (1996) and Salmon and Pipe (1997), who used the same questions when re-interviewing. Steward et al found that only half the details in each later interview had been mentioned previously and only a quarter was present in all three interviews.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations